IMPLEMENTATION OF INNOVATION AND INVESTMENT PROJECTS IN AGRICULTURAL INDUSTRY: COMPETITIVE ADVANTAGES AND RISKS - ROMANIUK, Oleksandr; LUNKIN, Valerii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Unsustainable development of the agrarian sector of the economy, low level of technical equipment of farms, technological backwardness of most enterprises, and several other factors currently restrain the innovative development of agricultural production, which affects the competitiveness of domestic agricultural products. Under these conditions, the primary task is a well-founded choice of priority directions for the innovative development of agriculture. For agriculture as a system that has its specificity, which is manifested in direct dependence on natural and climatic conditions, seasonality, and characteristics of the technological process, the issue of finding sources of investment attraction, the use of investment resources to revive innovative activity in agricultural organizations, which will contribute to the restoration of the reproductive process in agriculture. It is noted that the solution to these problems is possible under the condition of necessary compliance with investments and innovations and the close interaction of investment and innovation processes in agriculture. However, implementing such projects is associated with several risks that require careful analysis and management. The effective long-term activity of organizations, ensuring high development rates and increasing competitiveness, is primarily determined by the level of their innovative activity and the range of investment activities. Innovations create new opportunities for accelerated growth of the agricultural sector of the economy, as well as new threats and risks for agricultural enterprises. Other ways of achieving success are being formed, the competitive environment is becoming more arduous, and high flexibility in decision-making is required. The need for innovative development of agro-industrial complex enterprises is due not only to new opportunities that open up to the enterprises of the industry but also to the need to overcome internal and external risks and challenges that complicate the functioning of enterprises. Business entities should use internal reserves, intensify innovative activities, and consider innovative development as the primary strategic goal of enterprise development. The search for innovative ideas should be permanent, and innovative investment projects should be considered an opportunity to gain a stronger market position.
Keywords: innovation; investment; development; risk; resources; technologies